Pemanfaatan Media Sosial Dan Aplikasi Keuangan Digital Bagi Anggota Kelompok Pengrajin Batik Difabelpreneur Tanjung Jabung Barat Provinsi Jambi - Ade Jermawinsyah Zebua; Azwar Anas; Ahmad Fithoni; Istiqomah Malinda SB (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The Rindani Jambi Batik Craftsmen Group consists of disabled craftsmen (Specialpreneurs). In carrying out the activities of MSME members, they still use simple bookkeeping records manually, this makes it difficult to manage finances and find out the financial performance of partners. Manual bookkeeping is also less efficient in terms of time, especially as a batik craftsman, most of the time is used for the production process. Facts in the field were also found that members of MSME batik craftsmen in their marketing activities had not made optimal use of social media for business promotion, obtaining information and connecting with consumers. This Community Based Empowerment (PBM) service aims to educate and improve the skills of Specialpreneur MSMEs in using social media and digital financial applications independently. It is hoped that the benefits of PBM will facilitate the business activities of batik craftsmen, which in turn can increase income and improve the welfare of members of the Specialpreneur group. Lecture method and direct practice in creating websites and using financial applications. The results of the service show the ability of disabledpreneurs to utilize the Strawberry Kasir digital financial application in business and use it in real business. The Rindani batik craftsmen group already has a website account https://rumahrindani.com/ to reach a wider range of consumers and/or potential consumers.